Communal irrigation systems in South-Eastern Africa: findings on productivity and profitability - Pittock, Jamie; Bjornlund, Henning; Stirzaker, Richard; Rooyen, Andre F. van (Informa UK Limited, 2017)
Significant expansion of irrigated agriculture is planned in Africa, though existing smallholder schemes perform poorly. Research at six schemes in Mozambique, Tanzania and Zimbabwe shows that a range of problems are exacerbated by poor management, with limited market linkages leading to underutilization and a lack of profit. Improving sustainability of these complex systems will require: multiple interventions at different scales; investing in people and institutions as much as hardware; clarity in governments’ objectives for their smallholder irrigation schemes; appropriate business models to enable farmers; and better market linkages.